Jim Crow Laws in Langston Hughes’ “Breakfast in Virginia” and “Trouble with the Angels” - Listiyaningsih Listiyaningsih (Universitas Gadjah Mada, 2012)
This graduating paper analyzes Jim Crow laws as reflected in Langston Hughes’ short stories “Breakfast in Virginia” and “Trouble with the Angels”. This study aims to identify the practice of Jim Crow laws as seen in “Breakfast in Virginia” and “Trouble with the Angels”. This graduating paper applies mimetic theory proposed by Abrams since it is the most suitable approach to be used to analyze the connection between the literary work and the reality. There are two types of data which are used in this paper. The primary data are the short stories entitled, “Breakfast in Virginia” and “Trouble with the Angels”. Meanwhile, the secondary data are the references that support the analysis and are taken from the internet browsing.Based on the data analysis, this research concludes that segregation is the practice of Jim Crow laws in these two short stories. The segregations are clearly seen mostly in public places. In “Breakfast in Virginia” the segregations happen in the train, specifically in Jim Crow car and in the dining car in Virginia. Meanwhile, in “Trouble with the Angels” the segregations are clearly visible in the hotel and in the theater in Washington. In “Breakfast in Virginia” the segregations are faced by African American soldiers during World War II. Meanwhile, in “Trouble with the Angels” the segregations are experienced by African American actors and the other African American citizens of Washington. These two short stories show that Jim Crow laws made African Americans life getting worse, especially in public places. Both in “Breakfast in Virginia” and in “Trouble with the Angels”, African Americans cannot use the same public facilities as the whites. They can only use public facilities specially provided for the African Americans which have improper conditions. During the practice of Jim Crow laws, their rights are denied. This is proved by the segregations that do not only restrict African Americans from middle or low class status but also restrict those who have a higher status regardless their influential contribution toAmerica. This condition is painful for them.